Mi cuerpo como territorio de preguntas Institución Educativa Nuevo Latir (2018)
There are few researches that seek to understand the relationship of the thinking, acting and sentient body, starting from the narrative experiences, as is the case of this research on the body and its possibilities, seeking to enhance each dimension of the human being. When you talk about yourself is something difficult, that is why it is worth highlighting, that in this writing you will find situations where paradigms are broken, possibilities of expression of feelings are discovered, to lighten the soul and above all reencounter with itself. Then, within a theoretical research framework about the artistic body and its possibilities, from a pedagogical perspective we could say that the artistic passion anchored to the experiences, changes and transformations of the stages of the development of man, it is important to resignify defining moments of life , so that the knowledge is emergent from the own experience. The dance with its humanizing role, plays an important role in this research work, as a communicating conduit, to bring out feelings that can correct the soul and thus have tranquility and inner peace. Our body always has something to tell and shouts a thousand winds its desire for continuous exploration, to be heard and enhance everything it can provide, it is there, where the sense of the body, acquires an infinite value in the evolution of thought and existence human